KEUANGAN SOSIAL ISLAM DALAM MENGHADAPI WABAH COVID ??? 19 - Darsih Ahmadan (LA RIBA: Jurnal Perbankan Syariah, 2020)
Islamic Social Finance has an important position in overcoming the socio-economic problems of the community and helping the government overcome the covid problem -19 As a country with the largest Muslim majority, it can maximize the potential of Islamic social funds managed by Zakat, Infaq and Alms Management Organizations (OPZIS), managing institutions waqf (LPW) and microfinance institutions or Baitul Mal wat Tamwil (BMT). ZIS funds are empowered to provide basic basic needs, such as the provision of staple food, protective equipment for health and hygiene, in this condition the community is disrupted from the economic side. Waqf funds or assets can be empowered to help provide good sanitation facilities in the community and to provide clean water sources. If possible, endowment funds can also help provide health equipment that has continuous benefits such as breathing aids, ventilators or other needs. Furthermore, the role of BMT provides financial stimulus such as the distribution of benevolent loans or qardhul hasan, leeway in cooperation agreements (mudharabah) that can help the community to run micro businesses again. Slowly but surely the wheels of the economy of the lower classes will not stop if this solutive step is carried out. The Waqf Institution can also provide a development role by providing labor intensive programs to absorb labor, MSME business development land and also commercial projects.